A Comparison Between Young and Elderly Adults Investigating the Manual and Oral Capabilities During the Eating Process. Issue 4 (8th July 2016) - Laguna, Laura; Aktar, Tugba; Ettelaie, Rammile; Holmes, Melvin; Chen, Jianshe
Abstract: The adequacy of food handling and eating performance is vital for human survival and well‐being. However, physiological weakness due to ageing can often lead to compromised living. This work investigated quantifiable parameters to find associations between age and the eating capability in young ( n  = 36) and elderly sample populations ( n  = 40). The primary focus was to evaluate the strength of hand (hand and finger grip), mouth (tongue pressure) and the capability of texture discrimination (touch sensitivity and gel firmness). It was observed that, with age increment, there was a decrease in all measured forces (hand, finger, tongue) and an increased threshold in the texture discrimination (tactile and pair comparison test); the most decreased capability was observed in elderly women. Further statistical analyses show that hand grip force was related to finger force, tongue pressure and texture discrimination. These results demonstrate that a clear physiological separation exists between the two age groups and that the eating capability of an elderly individual can be objectively evaluated. Practical Applications: It is well understood that the elderly population is particularly vulnerable to malnutrition through decreased appetite which as a consequence affects health status. The level of proficiency in the associated food manipulation, mastication and deglutition executed during the process correlate with the eating proficiency or capability. To date, to the authors knowledge, there are no studies which address the eating capacity of the elderly population. It was observed that with increasing age, a corresponding decrease in deliverable force using the hand, finger and tongue was noted. Accompanying these findings, an increase in the threshold in texture discrimination (i.e., tactile and pair‐wise comparison tests) was also found with the elderly female group exhibiting the greatest reduction in capacity. The findings in this work offer objective measures with which to develop novel foods specifically aimed at improving nutritional products for the elderly.